The in-service development of primary school teachers in the use of computers in education with special reference to computer assisted learning: a case study - Murray, John Charles (Rhodes University, Faculty of Education, Department of Education, 1992)
Many white primary schools in South Africa have acquired computers which are being used in various ways. In my experience few members of staff are confident enough to use the computers in the school for educational purposes. Those who have been using them, generally have been doing computer literacy. The teachers in our school expressed the view that they would like to be able to use the computer, but that they lack the necessary skills and therefore would welcome some form of training. In my opinion computers should form an integral part of a child's learning environment. It has, for some time formed a part of his social environment, either in the home or in the workplace. For computers to be used effectively in the classroom, it follows that the teachers need to be trained to use them. In an attempt to overcome this problem, I designed and presented an in-service course, which used selected computer assisted learning (CAL) programs with teachers. These teachers then used these programs with the pupils in their class and evaluated the pupils' reactions to the innovation. As a result of the observations and the feedback provided by the sample of teachers, it is suggested that this might be a possible approach to in-service training for other schools. With adaptation it should be possible to follow this approach in any school which has a computer and someone on the staff who is willing to take the initiative to implement such an innovation.
Keywords: Education, Elementary -- South Africa -- Data processing; Computer-assisted instruction; Teachers -- In-service training -- South Africa